'JUST A WORD ON A STAVE AND THERE IS THE OPERA': THE INTERACTION BETWEEN MUSIC AND LIBRETTO IN PHILIP VENABLES' 4.48 PSYCHOSIS. (October 2021) - Crathorne, Tom
Abstract: The success of Philip Venables' opera adaptation of Sarah Kane's 4.48 Psychosis is underpinned by its powerful presentation of the play's text. This is predominantly facilitated by the other musical forces present, rather than through clever text-setting alone. Venables uses an array of timbral techniques, theatrical performance directions, referential sound effects, interactions with literary devices in the text and allusions to other musical genres in the opera to support and supplement his vocal writing. This article argues that the instrumental composition in 4.48 is critical in ensuring comprehension of the libretto and that, because of his working methods, Venables' adaptation is faithful to Kane's sensitive play.